Intra-subject investigation into the role of dental plaque induced IL-8, IL-6 and IL-1α expression and its association with the subgingival plaque microbiome - Tariq, Maheen (2022)
Aims: The study aims to evaluate the subgingival plaque microbiome composition and measure the GCF level of the IL-8, IL-6, and IL-1α of healthy and periodontitis sites in the same periodontitis subject. The study also explored the association between subgingival plaque composition and GCF levels of IL-8, IL-6, and IL-1α at periodontitis and healthy sites. Materials and methods: This study included 34 periodontitis subjects to collect the subgingival plaque and GCF samples from the periodontitis and healthy sites. The extracted DNA from dental plaque was sent to Illumina lab for 16s rRNA metagenomics. The V₃ and V₄ region of 16s RNA were amplified. The library was sequenced with MiSeq System, and data was analysed using MiSeq Reporter software (Illumina, San Diego, CA). After, quality filtering 313480 sequences were obtained and arranged in OTU based on 97% threshold. The GCF samples were analysed using ELISA to measure the level of IL-8, IL-6 and IL- 1α. The optical density was determined, and standard curve was generated using a four-parameter logistic curve fit. Results: The analysis of 16s rRNA revealed that periodontitis sites showed a higher species diversity than healthy sites. Moreover, there was no apparent clustering of healthy and periodontitis samples. Total 19 phylum, 142 genera, and 56 species were detected. The ELISA results show a trend of higher IL-8 and IL-6 concentrations in periodontitis sites and higher IL-1 concentrations in healthy sites. However, the differences between healthy and periodontitis sites were not statistically significant. Moreover, there was also a trend of positive and a negative correlation between periodontal parameters (PPD, CAL, and BOP) with IL-8, IL-6, and IL-1α. However, these findings were not statistically significant. The correlation between IL-8, IL-6, and IL-1α and bacterial species was also investigated. Our results show a statistically significant correlation (a mix of negative and positive correlation) between some bacteria species and cytokines (IL-8, IL-6 and IL-1α). For example, at the periodontitis site, IL-8 showed a statistically significant strong positive correlation with Bacillus thermoamylovorans. Conclusion: These findings suggests that certain microbiome may possibly cause the host immune system to secrete pro-inflammatory cytokines such as IL-8, IL-6, and IL-1α. Moreover, disease-related bacteria such as Phlyum (Spirochaetes, TM7 and Synergestetes), genus (Porphyromonas, Filifactor, and Peptococcus) and species (Prevotella intermedia, Prevotella copri, Prevotella nanceiensis, and Treponema socranskii) may be found abundantly in healthy sites and may help in the shift from healthy to periodontal disease.